Physical and Mechanical Properties of Mediumdensity Fibreboards Using Soy-Lignin Adhesives - M., Nasir; Gupta, Arun; Beg, M. D. H.; Chua, Gek Kee; A., Kumar (Forest Research Institute Malaysia, 2014)
Emission of formaldehyde from wood-based composites is a serious concern for research. In this study, nine different combinations of soyâlignin-based adhesives were prepared by varying their pH and soy content. Lignin was extracted from rubberwood fibres by an enzymatic treatment. Physical and chemical properties of the soyâlignin adhesives were investigated. Solid content in soyâlignin adhesive was calculated by oven-dry method and viscosity was studied using a digital viscometer. Fourier transform infrared spectroscopy was performed to study the structural changes in treated lignin and modified soyâlignin adhesives. Medium-density fibreboard (MDF) was prepared using the nine different soyâlignin adhesives and its bending and internal bonding properties were tested. It was observed that wood composites prepared by alkali-treated soyâlignin adhesives had improved properties. Scanning electron microscope was used to study the surface morphology of MDF. All samples were tested according to ASTM D1037-06a standards. The boards prepared using alkali soyâlignin adhesives passed internal bonding and modulus of rupture tests.